2007
DOI: 10.1111/j.1365-2934.2007.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring for each other: how do nurse managers ‘manage’ their role?

Abstract: The results showed a strong support system within the participant group, despite evidence in the literature that nurses, generally, are not supportive of each other. The results of this study may be used in the development of more effective support mechanisms for nurse managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 24 publications
1
63
0
Order By: Relevance
“…Indeed, both quantitative and qualitative studies published in the field of nursing management have dealt with distress and suffering at work, [2,6] structural factors, [5] factors in employee attraction and retention, [7] emotional health, [9] organizational structure, [14] factors that influence the NM's practice environment, [1,3] and NMs' lack of influence at work. [17][18][19] However, none of these studies have linked these factors to QWL specifically.…”
Section: Overview Of the Scientific Literature On Qwl In The Disciplimentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, both quantitative and qualitative studies published in the field of nursing management have dealt with distress and suffering at work, [2,6] structural factors, [5] factors in employee attraction and retention, [7] emotional health, [9] organizational structure, [14] factors that influence the NM's practice environment, [1,3] and NMs' lack of influence at work. [17][18][19] However, none of these studies have linked these factors to QWL specifically.…”
Section: Overview Of the Scientific Literature On Qwl In The Disciplimentioning
confidence: 99%
“…They must also regularly update their professional management skills to meet ministerial and organizational requirements for optimal management of the work environment for the benefit of nursing staff, on the one hand, and of both accessibility and continuity of care and services for the benefit of the population, on the other. [21] In reviewing the scientific literature, [12][13][14][15][16][17][18][19][20] we found that a significant amount of NM time is spent on the administrative management of operations, including staff training, work schedule management, mentoring, substitutions, completion of forms of all kinds, participation in meetings, drafting of minutes, checking payroll, supervision, and mail delivery. Finally, striking a balance between their clinical and administrative roles was essential for NMs to assume their clinicaladministrative leadership within the organization.…”
Section: Nms' Scope Of Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In this country, nurses with higher work and management experiences are more likely to be selected as nursing managers. Meanwhile, the Australian nursing and midwifery federation also holds courses to enhance communication and management skills of nurses (22,23). In the United Kingdom, governmental and non-governmental organizations outside the national medical system of the country, such as the center for excellence in services and the national institute of health, carry out research on the characteristics of nursing managers and help them meet selection criteria through a feedback to service delivery units (24,25).…”
Section: A: Selectionmentioning
confidence: 99%
“…Espinoza et al (2009) claim that unprepared nurses filling clinical leadership roles are a result of the healthcare organization's call to urgency in filling increased and lengthy vacant NL openings. Thus, researchers have found that NLs are not equipped with the skills and preparation needed to be effective clinical leaders and therefore undertake a trialand-error approach in learning to manage through the unknown of effective leadership, with much "learning about leadership occurring after an individual undertakes the role (Paliadelis, Cruickshank, & Sheridan, 2007). This form of trial-and-error approach of leadership learning managed through by the NL is connected to the action learning (Allen & Hartman, 2008) approach to leadership development identified earlier in this literature review.…”
Section: Nurse Leader Developmentmentioning
confidence: 99%